Communicating security? Policing urban spaces and control signals. (November 2014) - Barker, Anna
The rise of reassurance policing in the UK, informed by ideas drawn from a Signal Crimes Perspective, replaced a narrow focus on controlling crime with a broader emphasis on communicating security. This paper provides a sympathetic critique of dominant assumptions implied in this policy shift concerning the reassurance function of policing. Important in these theoretically informed policy debates is the idea that the police and their partners, through symbolic communications, can influence the extent to which individuals perceive that order and security exist within urban spaces. The paper draws on research findings to illustrate the contrasting ways visible signifiers of crime and formal controls are received and interpreted by diverse audiences. It challenges assumptions about the impact of criminal activities upon perceptions of safety and contributes insights into the unintended effects of formal controls that have implications for our understanding of local social order.